Food subsidies in the Philippines: Preliminary results - Garcia, Marito (International Food Policy Research Institute, 1988)
Evidence from countries like Sri Lanka and Egypt has shown that the fiscal costs of food price subsidy programs may be high, and once introduced, their termination may be politically difficult (Gavan and Sri Chandrasekera, 1979; Alderman, von Braun, and Sakr, 1982). On the other hand, if they are carefully designed and properly targeted, their effect on food consumption and nutrition may be significant. Although a food price subsidy scheme may sometimes present the most cost-effective approach to calorie or protein deficiencies, the introduction of such a program should be based on solid evidence regarding its cost effectiveness both in absolute terms and relative to alternative programs.